Perceptions of childcare staff for preventing overweight in Mexican preschool children: A SWOT analysis - Doris Verónica Ortega-Altamirano; Guadalupe Rodríguez-Oliveros; Marco Aurelio González-Unzaga; Hortensia Reyes-Morales (Instituto Nacional de Salud Pública, 2018)
Objective. To identify strengths, weaknesses, opportunities, and threats (SWOT) perceived by childcare staff for preventing childhood overweight. Materials and methods. Qualitative study using an interpretative phenomenological approach; 18 in-depth, semi-structured interviews and 12 focus groups with 89 key informants working in six Mexican public childcare centers (CCC) were conducted. Through content and SWOT analyses, experts further ranked fifty-nine recurrent perceptions regarding healthy feeding and physical activity (PA), using the Delphi method. Results. Strengths: Acknowledgement of the CCC's responsibility in fostering healthy feeding, availability of organizational regulations, and access to PA infrastructure/indoor activities. Weaknesses: Disregard of preschool overweight as a health problem, nutritional misperceptions, and perceived risk of child injuries while conducting PA. Opportunities: Willingness to reduce children's access to junk foods, and parental active play with children during weekends. Threats: Limited family nutritional education, and restricted parental time/economic constraints/ access to safe public spaces for PA. Conclusion. The identified SWOT must be considered when developing obesity-prevention interventions targeted at CCC.